Analysis of the Relationship Between Digital Service Quality, Perceived Value, and Loyalty in the Public Sector: A Study at Social Security Administrator for Employment (BPJS Ketenagakerjaan) Yogyakarta Branch - Zikra Merjanti (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2026)
This study examines the relationships among E-S-Qual, perceived value, and customer loyalty among users of the BPJSTKU application at BPJS Ketenagakerjaan Yogyakarta Branch. A quantitative approach was applied, using data collected from 200 respondents through structured questionnaires measured on a five-point Likert scale. The data were analyzed using Structural Equation Modeling (SEM) with AMOS 23. The findings reveal that E-S-Qual has a positive and significant effect on both perceived value and customer loyalty. Additionally, perceived value significantly influences customer loyalty and serves as a mediating variable in the relationship between E-S-Qual and customer loyalty. These results emphasize the critical role of electronic service quality in shaping customer perceptions and strengthening loyalty. This study contributes to the literature by confirming the mediating role of perceived value and offers managerial insights for enhancing digital service performance.